Supplying Barcelona: The Role of Public Market Halls in the Construction of the Urban Food System. (September 2022) - Fuertes, Pere; Gomez-Escoda, Eulalia M.
The origin of Barcelona's food system can be determined at the time when open-air markets were moved to covered spaces. Since then, market halls have adapted to many different scenarios: they have been the built form of public support for food sanitary control, a guarantee of quality and variety of edibles or a tool for the regeneration of urban fabrics. While in the second half of the twentieth-century comparable market systems in other European cities began to decline, half of the thirty-eight active markets at the end of the 2010s were built out of time in the city as a result of a public policy that accompanied urban expansion through the consolidation of small neighborhood centers. With the development of the so-called "Barcelona model" of regeneration of public space in the 1990s, markets became key pieces for urban transformation through food supply systems, a strategy still in force today.